Association between individual characteristics, body image and symptoms of eating disorders in nutrition students from a higher education institution (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
Currently, with the notoriety of specific beauty standards, there is the pressure exerted by society to follow them. Nutrition academics are a population group that suffers from this pressure, which can influence eating behavior. The objective of this study is to verify the relationship between the symptoms of eating disorders and the perception of body image in Nutrition students, according to individual characteristics. Quantitative study with a cross-sectional design, with the application of an online questionnaire, using the Eating Attitudes Test-26 (EAT-26), the Brazilian Silhouette Scale and the socioeconomic questionnaire. Descriptive and analytical statistics were performed to verify possible associations with the outcomes. A total of 72 students from the nutrition course participated in the study, with a mean age of 23.4±3.8 years, and it appears that 58.3% belong to the middle economic class. According to the EAT-26, 34.7% of the students showed signs of risky eating behavior for eating disorders. The Brazilian Silhouette Scale revealed that 79.2% have body size distortion. It was found that the socioeconomic stratum is related to the symptomatology of the development of eating disorders and dissatisfaction and distortion of body size (p
Keywords: Feeding Behavior; Body Image; Perception; Distortion